Interatomic relaxation processes induced in neon dimers by electron-impact ionization - Yan, Sheldon; Stumpf, Vasili; Gokhberg, Kirill (Physical review, 2018)
We report an experimental observation of the interatomic Coulombic decay (ICD) and radiative charge-transfer (RCT) processes in a Ne dimer (e,2e) following a 380-eV electron impact. By detecting the Ne+−Ne+ cation pair and one of the emitted electrons in coincidence, the fingerprint of the ICD process initiated by the inner-valence ionization of Ne is obtained. Furthermore, the experimental results and ab initio calculations together unambiguously confirm the occurrence of the RCT process, and we show that most of the low-energy electrons produced in ionization of the Ne dimers are due to the ICD, which strongly suggests the importance of the ICD in causing radiation damage in a biological medium.